Implications of a conserved region of bluetongue virus protein VP2 in cross-neutralisation of bluetongue virus serotypes - Jyothi, Shiva J. (Onderstepoort J Vet Res, 2020)
Bluetongue (BT) is a vector-borne disease of ruminants caused by Bluetongue virus (BTV). Twenty-nine different serotypes of BTV are currently reported throughout the world. The main objective of this study is the development of a subunit vaccine model that could potentially be adapted to provide broad spectrum protection against multiple BTV serotypes, which the conventional vaccines fail to address. To this end, three different BTV proteins (conserved region of viral protein [VP]2, VP5 and NS1) were expressed and purified in an Escherichia coli expression system. The immunogenicity of these proteins was tested in murine models using the Montanide(TM) ISA 201 VG adjuvant. BALB/c mice were immunised thrice (with individual proteins and a mixture of three proteins) at two-week intervals and were monitored until Day 40 post-infection/vaccination. Protein-specific antibodies directed against the recombinant proteins were detected by indirect enzyme-linked immunosorbent assay. Neutralising antibody (Nab) titres and cross-neutralisation against a range of BTV serotypes (BTV-1, -2, -4, -5, -9, -10, -12, -16, -21, -23 and -24) were determined by serum neutralisation test. The recombinant proteins elicited higher Nab titres compared with the inactivated vaccine group, except for BTV-1, where the inactivated vaccine group elicited higher Nab titres. Additive effect of the three proteins was not observed as the Nab titres generated with a combination of conserved VP2, VP5 and NS1 was similar to those of the individual protein groups. Whilst BTV-12 could only be neutralised by serum raised against the inactivated vaccine group, BTV-5 and -24 could not be neutralised by any of the groups tested. Our cumulative data suggest that the conserved regions of VP2 (cVP2), VP5 and NS1 could play an important part in the novel vaccine design against multiple BTV serotypes. Importantly, given that VP2 was already known to elicit a serotype-specific immune response against BT, we report, for the first time, that the conserved region of VP2 has the ability to induce cross-protective immune response.